2018
DOI: 10.1111/crj.12757
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between smoking and total antioxidant status, total oxidant status, oxidative stress index, vit C, vit E

Abstract: The parameters of TAS, vitamin C and vitamin E were significantly higher in the non-smoker group than in the smoker group. The levels of TOS and OSI were higher in the smoker group. It is known that cigarette smoking leads to various diseases because of the free radicals it contains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 10 publications
3
30
0
Order By: Relevance
“…A recent metaanalysis indicated that the proportion of patients with lung cancer who continue to smoke after diagnosis ranged from 6 to 83% [35]. Mechanisms behind the association between smoking and fibrin clot properties in cancer patients remain to be established; however, most likely increased oxidative stress contributes to our observation [36]. Oxidative stress reflected by 8-epi-prostaglandin F 2α was enhanced in heavy smokers compared to never-smokers and strongly correlated with impaired fibrin clot properties in the former group [34].…”
Section: Discussionmentioning
confidence: 75%
“…A recent metaanalysis indicated that the proportion of patients with lung cancer who continue to smoke after diagnosis ranged from 6 to 83% [35]. Mechanisms behind the association between smoking and fibrin clot properties in cancer patients remain to be established; however, most likely increased oxidative stress contributes to our observation [36]. Oxidative stress reflected by 8-epi-prostaglandin F 2α was enhanced in heavy smokers compared to never-smokers and strongly correlated with impaired fibrin clot properties in the former group [34].…”
Section: Discussionmentioning
confidence: 75%
“…CS contains oxidative gases, PAHs and particulate matter, which are known to lead to endothelial inflammation through oxidative stress and carbon monoxide, which strongly binds to hemoglobin and therefore causes hypoxia (Fig. 17) [208,209]. However, nicotine alone has the ability to stimulate dendritic cells and monocytes, with the concomitant release of pro-inflammatory cytokines [210].…”
Section: Discussionmentioning
confidence: 99%
“…A novel finding in our study is that simply incubating fresh whole blood from smokers for 7 h without any exogenous stimulus increases the levels of a number of pro-inflammatory cytokines/chemokines, the most robust being IL-8. This ex-vivo generation of proinflammatory cytokines may be related to the higher levels of oxidative stress reported in cigarette smokers 42,43 . Cigarette smoking generates many reactive species, which may overwhelm the antioxidant defense system.…”
Section: Smoking Alters Innate and Acquired Immune Responsesmentioning
confidence: 92%
“…Cigarette smoking generates many reactive species, which may overwhelm the antioxidant defense system. While low molecular weight antioxidants such as vitamin E and C have been reported to be lower in smokers 42 , blood glutathione levels are 8-10% higher 44 . It is thus possible that cigarette smokers produce a compensatory level of glutathione to maintain a comparable in vivo level of cytokines/chemokines to non-smokers.…”
Section: Smoking Alters Innate and Acquired Immune Responsesmentioning
confidence: 96%